Habiter confinés, domestiquer la pandémie : vers une nouvelle syntaxe habitante ? - Élise Roy; Julie Gangneux-Kebe; Léa Perraudeau (Développement Durable et Territoires)
Based on the analysis of detailed observations of a « confined living » carried out by students in a school of architecture, this article aims to document the experience of the pandemic, a real collective test calling into question the relationships maintained with our daily spaces. which are both material and social. If the analyzes conducted here highlight phenomena that are already known, they also highlight renewed appropriations that could be permanently part of a new « inhabitant syntax », making room for telework, and supporting a revealed relationship with the outside in all its importance. By depriving us of a broad spatial repertoire, confinement has led us to recompose our territorialities and to an unprecedented evaluation of our material framework and the value of our spatialities.